Biomechanics of PHILOS plates in Vancouver B1 periprosthetic femoral fracture - Yun, Changjun; Qian, Wenjie; Zhang, Jie; Zhang, Wen; Lv, Jinpeng (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: To investigate the clinical efficacy of PHILOS plates in the treatment of Vancouver B1 periprosthetic femoral fracture (PFF) and to validate its biomechanical reliability via finite element analysis and mechanical testing on the Synbone femoral models. Methods: Ten males and eight females with Vancouver B1 PFF who underwent PHILOS plate fixation between September 2017 and January 2022 were selected. The average age was 72.61± 8.19years, with a range of 57 to 86 years old. X-ray films were taken to assess the fracture healing situation around the femoral prosthesis as well as the position of the PHILOS plates and femoral prosthesis. Two different plates (the PHILOS plate and the Cable GTR plate) were used for fixation, and the differences in biomechanical stability of the two fixation methods were compared using finite element analysis and mechanical testing on the Synbone femoral models to validate the biomechanical dependability of the PHILOS plate. Results: All 18 cases were followed for at least one year, as a result. The average period of follow-up was 17months, ranging from 12 to 36 months. At the most recent follow-up, Harris scores for the hip joints of patients ranged from 82 to 89, with an average score of 86. The X-rays revealed that all fractures surrounding the femoral prosthesis had healed and that there was no looseness in the femoral prosthesis. None of the PHILOS license plates had expired. All patients were able to perform full-load walking, and pain and claudication in affected limbs were significantly reduced. Finite element analysis and mechanical testing of the Synbone femoral model revealed that the fixation effect of the PHILOS group was superior to that of the Cable group; consequently, PHILOS plates can be used to effectively fix fractures around the proximal femoral prosthesis. Conclusion: PHILOS plates are initially used in the treatment of Vancouver B1 PFF, which may be a good choice due to their simpler operation, lower medical costs, and satisfactory clinical efficacy.